مطالعه بیماری ژنتیکی پیچیدگی ستون فقرات (CVM) و نقص در آنزیم اوریدین مونوفسفات سنتاز در گاوهای سرابی (DUMPS) با تکنیک PCR-SSCP و PCR-RFLP - Mohammad Reza Nasiri; Shahrokh Qovvati; Mojtaba Tahmoures Pour (مجله بیوتکنولوژی کشاورزی, 2009)
Evaluating and detection of genetic disorders is very important in both human and animal communities. Blood samples were prepared from 162 cows from Sarabi cows’ research station in Sarab, East Azerbaijan province, Iran. DNA extraction was done based on guanidine thiocyanate – silica gel method. The aim of this study was to identify the CVM and DUMPS carriers in Sarabi native cows of Iran. Standard polymerase chain reaction was applied to amplify a 177 bp and a 108 bp fragments from exon 4 in SLAC35A3 gene and exon 5 in UMPs gene using specific primers pair. The SLC35A3 gene PCR products were analyzed using single stranded conformation polymorphism (SSCP) to reveal their mutations on polyacrylamide gel. In order to identify DUMPS carrier animals, a RFLP assay was conducted and the UMPs PCR products were digested by AvaI restriction enzyme. Results indicated that no G→T mutation at position 559 in exon 4 of SLAC35A3 gene and C→T mutation at position 405 in exon 5 of UMPs gene in examined cows respectively and subsequently no carrier was identified.